The Potential of Low-Rise Dense Typologies for Post-COVID-19 Urban Housing Spatial Planning: A Case Study of Nablus, Palestine - Itma, Mohammed (Journal of Architectural/Planning Research and Studies (JARS), 2025)
Based on the global concern regarding human health in residential areas since 2020, this study delves into the potential of traditional low-rise dense typologies as a viable solution for post-COVID-19 housing spatial planning in Middle Eastern Mediterranean countries. Such typologies are found in the traditional architecture of Nablus City, Palestine. They are characterized by their horizontal stratification and distribution of courtyards through them, which offers a promising avenue for fair distribution of populations and avoiding crowded points in urban housing. The study seeks to elucidate the advantages, challenges, and applicability of low-rise dense typologies for future housing design in Palestine. It also aims to confirm their primary characteristics that can assist in limiting the spread of epidemics. Accordingly, the study analyses these typologies in Nablus City. It uses architectural analysis to verify its ability to enhance self-sufficiency, manage densities, facilitate isolation and quarantine, and encourage stay-at-home in residential areas. The survey results show that such typologies are characterized by mixed-use, activity-based densities and avoid crowding, support passive environmental systems, and facilitate flexible layouts for future design. The study also surveys expert opinions to confirm the research results and allocate factors such as spatial organization and community integration through empirical data collected in Nablus City. Accordingly, the study’s main finding is that low-rise dense typologies are a high-potential approach for future housing if designed in a contemporary way that preserves traditional values. Proposed guidelines for a modern architectural model are presented, which can be used in many similar urban environments.